Pasanggiri Damas: A Strategy To Preserve Tembang Sunda Cianjuran Art in West Java, Indonesia - Julia, Julia (Universitas Negeri Semarang, 2018)
This article aims at analyzing a vocal contest of a traditional musical art genre namely Tembang Sunda Cianjuran (Cianjur Sundanese Traditional Song) in West Java, Indonesia. The contest, also known by the term PTSC DAMAS, had been held continuously since 1962 by youth social organization called DAMAS (Daya Mahasiswa Sunda). The study was conducted using qualitative approach. Data was collected through observation, interviews, and documentation. Data analysis was conducted by using an interactive model. The results show that PTSC DAMAS has greatly affected the preservation and development of the Tembang Sunda Cianjuran, not only in the music accompaniment but also vocal aspects. Various parties has been very supportive of PTSC DAMAS, thus the contest can be carried out consistently.